2019
DOI: 10.4012/dmj.2018-137
|View full text |Cite
|
Sign up to set email alerts
|

Surface wettability and nano roughness at different grit blasting operational pressures and their effects on resin cement to zirconia adhesion

Abstract: This study analyzed the effect of grit blasting pressures on resin cement to zirconia (ZrO2) adhesion using enclosed mold shear bond test (EM-SBS). ZrO2 blanks were pre-treated with Rocatec ™ Soft as follows: group 1: control, group 2: specimens treated at 80 kPa, group 3: at 180 kPa, group 4: at 280 kPa, and group 5: at 380 kPa. Monobond ® N and Multilink ® Speed were used as the silane and resin cement, respectively. Next, the blanks were assigned into three subgroups (n=8, N=108) according to storage condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Their relationship that an increase in one increases another and vice versa has been well known and shown in the researches regarding dental zirconia [12,13]. To understand the effect of surface roughness and contact angle on zirconia, various processes such as laser scanning, sandblasting, polishing, machining, and heat treatment were performed to produce diverse topography [14][15][16]. However, the effect of repeated firing on the surface roughness and contact angle of zirconia has not been studied yet.…”
Section: Introductionmentioning
confidence: 99%
“…Their relationship that an increase in one increases another and vice versa has been well known and shown in the researches regarding dental zirconia [12,13]. To understand the effect of surface roughness and contact angle on zirconia, various processes such as laser scanning, sandblasting, polishing, machining, and heat treatment were performed to produce diverse topography [14][15][16]. However, the effect of repeated firing on the surface roughness and contact angle of zirconia has not been studied yet.…”
Section: Introductionmentioning
confidence: 99%
“…In the present systematic review, the studies were conducted in vitro, and a great heterogeneity was observed among the studies. Despite the limitations of this type of study, it is necessary to evaluate the behavior of different materials and techniques before their clinical application [ 18 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies did not mention this step, they may have done it too. Ultrasonic cleaning before surface conditioning or the resin cement is also widely used [ 32 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. Likewise, several solutions were used, including distilled water, alcohol, acetone, ethanol, and isopropanol, with a usage time between 1 and 10 min.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations